Sistema de gestión de créditos en la AETPAM - APEPAM y descuentos del rol de pago de los servidores públicos de la ESPAM-MFL - Loor Vaca, Joselin Sebastiana (2021)
The objective of this degree work was to develop a web system to manage the credits that are made in the AETPAM - APEPAM and the discounts in the payment role of public servants for the Human Talent department at ESPAM-MFL, in order to fulfill this purpose, the agile development methodology Extreme Programming (XP) was used, which by having four phases (planning, design, coding and test) allowed the group to carried out in a collaborative and effective way; in the planning phase, the data collection was carried out to determine the main needs that had to be solved, in the design phase the interfaces were made according to the system requirements, in the coding phase the respective programming of each of the modules was made through unit and black box tests, using computer tools such as Visual Studio, ASP.NET and SQL Server and in the testing phase the respective verification of the correct operation of the system. Based on the results obtained in the performance tests, a comparative table was made between the time that certain tasks have been carried out with the system and without it, which showed that the system will provide a significant reduction in time, efficiency and immediacy in activities that the department and the associations carry out. In addition, how beneficial it will be for the institution.